The effect of PhET (Physics Education Technology)-assisted guided inquiry learning on grade VI learning interest and critical thinking skills - Mukarramah, Mukarramah; Sanjaya, Dewa Bagus; Suastra, I Wayan (Psychology, Evaluation, and Technology in Educational Research, 2025)
This study investigates the impact of the guided inquiry learning model, augmented by PhET (Physics Education Technology) media, on the critical thinking skills and learning interest of sixth-grade students in Science subjects at Islamic elementary school, Jembrana, Indonesia. The research was prompted by the observed deficiency in both aspects, attributed to conventional, passive, and non-interactive pedagogical methods. Utilizing a quantitative approach with a quasi-experimental design, the study divided subjects into two groups: an experimental class implementing PhET-assisted guided inquiry and a control class utilizing conventional methods. Data collection involved essay tests to measure critical thinking skills and Likert-scale questionnaires to assess learning interest. Multivariate Analysis of Variance (MANOVA) results indicated that the integration of guided inquiry and PhET media significantly influenced students' critical thinking skills and learning interest. The experimental group demonstrated higher mean scores. PhET media effectively visualized abstract scientific concepts, making them more tangible and comprehensible, while the guided inquiry model stimulated analytical reasoning and active student participation. This combined approach proved effective in enhancing student outcomes in science education.